Characteristics of Enterovesical Fistula Patients Visiting the Urology Department of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from 2015 to 2019 - Daniel Saputra; Tjahjodjati Tjahjodjati (Faculty of Medicine, Universitas Padjadjaran, 2021)
Enterovesical fistula (EVF) represents an abnormal channel between the intestine and the bladder. The EVF is a complication of inflammatory or neoplastic diseases and injuries. Diagnosis of EVF can be challenging and often delayed up to several months after the onset of the symptoms. This study aimed to determine the characteristics of patients with enterovesical fistula visiting Dr. Hasan Sadikin General Hospital Bandung, Indonesia. This retrospective descriptive study used the medical records of EVF patients treated in the urology department of Dr. Hasan Sadikin General Hospital from 2015 to 2019 as the secondary data to be analyzed. A total of 58 patients with EVF were enrolled in this study. By gender, that more than half of the patients were male patients (n=30, 51.7%) and 45% of patients were between 41 and 50 years old. The most common symptoms of EVF were pneumaturia and fecaluria which were seen in 30 (51.7%) and 20 (34.5%) patients, respectively. Twenty-nine (50%) patients experienced malnutrition and 18 (31.1%) patients had diabetes mellitus as a comorbid. The most common type of fistula was rectovesical fistula (n=45, 77.6%) and 26 (66.6%) patients suffered from rectosigmoid cancer and malignancy (68.95) had become the most predominant etiology. Escherichia coli was found in 42 (72.4%) urine cultures collected from the patients and cystoscopy with fistula biopsy was found in 43.1% of cases, followed by fistula repair (29.3%) and urethral catheter drainage (15.5%). Hence, malignancy and rectosigmoid cancer become the most common etiology of EVF while cystoscopy with fistula biopsy is the most frequently performed procedure.